Video role-play versus powerpoint lecture in the knowledge domain among medical students during the COVID-19 pandemic era: A systematic review and meta-analysis - Sungkono; Firdian Makrufardi; Annisa Fairuz Nur Azizah; Firdiawan Ekaputra (Journal of Education and Health Promotion)
The coronavirus disease 2019 (COVID-19) pandemic disrupted conventional teaching methodologies, forcing educational institutions to swiftly adapt to remote learning. This study aimed to compare the effectiveness of video- and powerpoint-based teaching methods in the knowledge of medical students using a systematic review and meta-analysis. A systematic review of the literature was conducted to identify relevant studies that compared the efficacy of video-based and PowerPoint-based teaching methods in medical students during the COVID-19 pandemic. PubMed, MEDLINE, and Embase were systematically searched, and studies published before October 2023 were considered. Fixed and random-effects meta-analyses were performed to calculate the pooled effect of estimates. All statistical analyses were performed using Review Manager software. The analysis included nine studies that met the inclusion criteria. We observed a significant effect of video-based education methods compared to powerpoint-based education methods, with a mean difference of 2.42 (95% CI: 2.09–2.75, P < 0.0001). Furthermore, our sensitivity analysis did not reveal a substantial alteration, with the mean difference remaining at 2.42 (95% CI: 2.09–2.75, P < 0.0001). After analyzing the funnel plot, no indications of publication bias were observed. Video role-play proved to be a powerful tool for knowledge acquisition among medical students during the COVID-19 pandemic. Lecturers should consider incorporating video role-play into teaching methods for asynchronous learning purposes.